2007
DOI: 10.1161/strokeaha.107.485441
|View full text |Cite
|
Sign up to set email alerts
|

The Met Allele of the BDNF Val66Met Polymorphism Predicts Poor Outcome Among Survivors of Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Brain-derived neurotrophic factor (BDNF) plays a role in neuronal survival, plasticity and neurogenesis. The BDNF gene contains a common Val66Met polymorphism; the Met allele is associated with lower depolarization-induced BDNF release and differences in memory functions and brain morphology. We hypothesized that the Met allele is associated with poor recovery from subarachnoid hemorrhage. Methods-A sample of 105 survivors was assessed at 3 months after subarachnoid hemorrhage using Glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 11 publications
8
71
3
Order By: Relevance
“…Therefore, as in other recent studies (Siironen et al, 2007;Soliman et al, 2010), we grouped patients with Val/Met and Met/Met genotypes. As a result, we cannot exclude the possibility that homozygous patients may have a worse outcome; this point should be further investigated in studies conducted in populations with a higher BDNF Met polymorphism rate, such as Asian populations (Pivac et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as in other recent studies (Siironen et al, 2007;Soliman et al, 2010), we grouped patients with Val/Met and Met/Met genotypes. As a result, we cannot exclude the possibility that homozygous patients may have a worse outcome; this point should be further investigated in studies conducted in populations with a higher BDNF Met polymorphism rate, such as Asian populations (Pivac et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, BDNF serum levels may be associated with cognitive impairment in schizophrenia (Zhang et al, 2012), or illness severity in major depression (Birkenhä ger et al, 2012). Moreover, it has been shown that the BDNF Met polymorphism may also affect recovery from hemorrhagic stroke such that it predicts a poor outcome among patients who survive an aneurysmal subarachnoid hemorrhage (Siironen et al, 2007). The BDNF Met polymorphism has not been assessed previously in patients in a VS after a TBI, although it was recently demonstrated that other BDNF polymorphisms (rs7124442 and rs1519480) might be useful for predicting general intelligence 10-15 years after a penetrating TBI (Rostami et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It modulates the response to rTMS, which may explain some of the individual differences in the effect of stimulation (176). It has also been proposed to be a predictor for poor outcome among survivors of aneurismal subarachnoid hemorrhage (177). There are likely to be other genetic differences that can influence outcome.…”
Section: Genetic Polymorphismmentioning
confidence: 99%
“…It is certainly not surprising that there is also a genetic background for the possible extent of brain plasticity as previously demonstrated by a BDNF val66met polymorphism, which distinctly modiWes experience-dependent plasticity in the human motor cortex [7]. In this context, it should be mentioned that the met allele of this polymorphism is also C. Sommer (&) Department of Neuropathology, Mainz University Medical Center, Langenbeckstrasse 1, 55131 Mainz, Germany e-mail: sommer@neuropatho.klinik.uni-mainz.de associated with poorer outcome after subarachnoid hemorrhage [11]. If physiological adaption is associated with such tremendous plastic changes, pathological stimuli like brain injury should potentially trigger plastic changes to an even greater extent.…”
mentioning
confidence: 82%